2011
DOI: 10.4236/ajac.2011.26075
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Cocaine and Crack Cocaine via Thin Layer Chromatography Coupled to Easy Ambient Sonic-Spray Ionization Mass Spectrometry

Abstract: Cocaine and crack cocaine are usually seized with a great diversity of adulterants, such as benzocaine, lidocaine, caffeine, and procaine. The forensic identification of cocaine in these drug mixtures is normally performed using colorimetric testing kits, but these tests may suffer from interferences providing false-positive or false-negatives. In this work, we describe the use of thin layer chromatography coupled to easy sonic-spray ambient ionization mass spectrometry (TLC/EASI-MS) for rapid and secure analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…[32][33][34][35][36] Our previous experiments revealed that the most common adulterants are levamisole, caffeine, lidocaine, phenacetine, and hydroxyzine. [32][33][34][35][36] Our previous experiments revealed that the most common adulterants are levamisole, caffeine, lidocaine, phenacetine, and hydroxyzine.…”
Section: Validation Of the Analytical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…[32][33][34][35][36] Our previous experiments revealed that the most common adulterants are levamisole, caffeine, lidocaine, phenacetine, and hydroxyzine. [32][33][34][35][36] Our previous experiments revealed that the most common adulterants are levamisole, caffeine, lidocaine, phenacetine, and hydroxyzine.…”
Section: Validation Of the Analytical Proceduresmentioning
confidence: 99%
“…Various adulterants are added to cocaine to increase the volume of the drug. [32][33][34][35][36] Our previous experiments revealed that the most common adulterants are levamisole, caffeine, lidocaine, phenacetine, and hydroxyzine. All the adulterants were well separated with other impurities as shown in Figure 4.…”
Section: Profiling Of Cocaine By Uhplc-qtof-msmentioning
confidence: 99%
“…EASI has already been successfully tested with different analytes in different matrices and in various forensic applications such as the aging of ink writings on paper surfaces , authenticity of perfumes , identification of fake banknote and vehicle documents , and analyses of m‐CPP and ecstasy tablets . EASI has also been coupled to thin layer chromatography (TLC) to study the presence of 3,4‐methylenedioxymethamphetamine (MDMA), methamphetamine, 3,4‐methylenedioxyethylamphetamine (MDEA), 3,4‐methylenedioxyamphetamine (MDA), amphetamine, caffeine, and lidocaine in street ecstasy tablets.…”
mentioning
confidence: 99%
“…EASI and its sister techniques have been used in a variety of applications; for (1) the direct analysis of drug, pills as exemplified for sildenafil (Figure a), and for the characterization of TLC spots, as exemplified for cocaine (Figure b), for the quality control and certification of geographical origin of olive oils; for direct fingerprinting control of forgery in perfumes; for the nearly instantaneous characterization of the composition of cationic surfactants and quality control of fabric softeners; for the analysis of biodiesel and biodiesel/petrodiesel blends in combination with high performance thin layer chromatography; for fingerprinting analysis of propolis; for the direct analysis of fuels; for the instantaneous characterization of vegetable oils via TAG and FFA profiles, in combination with selective sequesters based on molecularly imprinted polymers (MIP) for the analysis of phenothiazines in urine (Figure d); for the fingerprinting and aging of ink in forensic investigations; as a rapid and secure screening method for street illegal drugs; to characterize noble and endangered woods; for the direct monitoring of known and unknown (or unexpected) drug degradation products as a function of time and manufacturing process, as exemplified for enalapril maleate (Figure c), via thermal imprinting for the analysis of TAG profiles in meat matrices; for petroleomic studies of ‘untouched’ crude oil samples; for the forensic investigation of counterfeit money bills; and, in its Venturi version, for real‐time analysis of brain tissue . These are illustrative of the ‘whole world’ (see cover picture) application of modern ‘simpler’ MS.…”
Section: Easier Than Ever Msmentioning
confidence: 99%